Luther en Calvyn se siening van seksualiteit - P. J. de Bruyn (In die Skriflig, 1995)
Until the time of the Reformation in the sixteenth century the Roman Catholic view of sexual intercourse was that it is sinful in itself, but that this specific sin is pardonable when committed within a marital relationship for the purpose of procreation. At the Council of Trente it was determined that intercourse was not allowed within the three days preceding Holy Communion. Luther’s view, and to a great extent also that of Calvin, was that the act of sexual intercourse as such is sinful. Within a marital relationship, however, whether for the purpose of procreation or for the satisfaction of the sexual needs of husband and wife, this sin is pardonable - according to Luther and Calvin’s views. Luther stressed that participation in Holy Communion did not limit married people in this regard: moderation was the only norm. Both Luther and Calvin strongly rejected celibacy.